Factors Influencing The Readiness Of The Public And Private Sectors To Implement Public-Private Partnerships In Developing Affordable Housing In Yemen - Al Shareem, Khaled Mohammed Ahmed (2014)

(untitled)
Evidence shows that the adoption of a new system such as public– private partnerships PPPs mitigates the financial burden for governments and development of public services. PPPs have been extensively implemented worldwide and have become a vital issue in several studies. The adoption of PPPs to promote affordable housing in developing countries such as Yemen remains unknown. Bukti-bukti yang ada menunjukkan bahawa penggunaan sistem yang baru seperti perkongsian awam-swasta atau PPP mampu mengurangkan beban kewangan kerajaan dan pembangunan perkhidmatan awam. PPP telah dilaksanakan secara meluas di seluruh dunia dan ia telah menjadi satu isu penting dalam beberapa kajian yang telah dijalankan.